Quantitative CT: Associations between Emphysema, Airway Wall Thickness and Body Composition in COPD - Erica P. A. Rutten; Thomas B. Grydeland; Sreekumar G. Pillai; Scott Wagers; Asger Dirksen; Harvey O. Coxson; Amund Gulsvik; Emiel F. M. Wouters; Per S. Bakke (Pulmonary Medicine)
The objective of the present study was to determine the association between CT phenotypes—emphysema by low attenuation area and bronchitis by airway wall thickness—and body composition parameters in a large cohort of subjects with and without COPD. In 452 COPD subjects and 459 subjects without COPD, CT scans were performed to determine emphysema (%LAA), airway wall thickness (AWT-Pi10), and lung mass. Muscle wasting based on FFMI was assessed by bioelectrical impedance. In both the men and women with COPD, FFMI was negatively associated with %LAA. FMI was positively associated with AWT-Pi10 in both subjects with and without COPD. Among the subjects with muscle wasting, the percentage emphysema was high, but the predictive value was moderate. In conclusion, the present study strengthens the hypothesis that the subgroup of COPD cases with muscle wasting have emphysema. Airway wall thickness is positively associated with fat mass index in both subjects with and without COPD.